Empowerment of the Community of Candimulyo Village, Jombang Regency in Facing the Covid-19 Pandemic: Leading Product Innovation - Wuryan Andayani; Sutrisno T (Universitas Brawijaya, 2021)
Community empowerment is an effort to improve the ability of the community to become an empowered community to enhance the quality of life of the community. The people of Candimulyo Village were given training in making eco print batik and making dim sum food. The training is provided, hoping that the community will have the expertise to make eco prints and dim sum food, which can then be marketed and increase income for families and the community. Ecoprint is very easy to make because it uses natural materials grown around the house and uses environmentally friendly materials. The community is also expected to innovate to make food that can meet the needs of families and society at large and can innovate and develop eco prints. The results of eco prints are stunning and much in demand by the wider community and have high selling power. Eco prints can also be used as a Village Featured Product by creating a Village characteristic motif.